Răspuns :
a+b=21
b+c=30
a+2b+c= (a+b) +( b+c)= 21+30=51
(b+c) - (a+b)= b+c -a-b=c-a= 30-21=7
2a+3b+c= 2a+2b+ b+c= 2*(a+b)+(b+c)= 2*21+30=42+30=72
a+4b+3c =a+b+ 3b+3c= (a+b)+3*(b+c)=21+3*30=111
b+c=30
a+2b+c= (a+b) +( b+c)= 21+30=51
(b+c) - (a+b)= b+c -a-b=c-a= 30-21=7
2a+3b+c= 2a+2b+ b+c= 2*(a+b)+(b+c)= 2*21+30=42+30=72
a+4b+3c =a+b+ 3b+3c= (a+b)+3*(b+c)=21+3*30=111
a+2xb+c
a+b=21 b+c=30
a+b+b+c=21+30=51
2xa+3xb+c
a+b=21 b+c=30
2a+2b+b+c=2(a+b)+30=2x21+30=72
a+4b+3c
a+b=21 b+c=30
a+b+3b+3c=21+3(b+c)=21+3x30=111
a+b=21 b+c=30
a+b+b+c=21+30=51
2xa+3xb+c
a+b=21 b+c=30
2a+2b+b+c=2(a+b)+30=2x21+30=72
a+4b+3c
a+b=21 b+c=30
a+b+3b+3c=21+3(b+c)=21+3x30=111